2018
DOI: 10.1021/jacs.8b09257
|View full text |Cite
|
Sign up to set email alerts
|

How Do Enzymes Orient When Trapped on Metal–Organic Framework (MOF) Surfaces?

Abstract: Enzyme immobilization in metal–organic frameworks (MOFs) offers retained enzyme integrity and activity, enhanced stability, and reduced leaching. Trapping enzymes on MOF surfaces would allow for catalysis involving large substrates. In both cases, the catalytic efficiency and selectivity depend not only on enzyme integrity/concentration but also orientation. However, it has been a challenge to determine the orientation of enzymes that are supported on solid matrices, which is even more challenging for enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(139 citation statements)
references
References 50 publications
5
125
0
3
Order By: Relevance
“…Nevertheless, determining the orientation of enzymes is even more challenging for enzymes trapped in MOFs because of the interferences of the MOF background signals. Fortunately, characterization of the orientation information of the trapped enzymes within MOFs has recently been achieved by site‐directed spin labeling in combination with electron paramagnetic resonance spectroscopy (SDSL‐EPR) . This SDSL‐EPR technology may be helpful for studying the effect of orientation distributions of trapped enzymes on their bioactivity after encapsulation by a MOFs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, determining the orientation of enzymes is even more challenging for enzymes trapped in MOFs because of the interferences of the MOF background signals. Fortunately, characterization of the orientation information of the trapped enzymes within MOFs has recently been achieved by site‐directed spin labeling in combination with electron paramagnetic resonance spectroscopy (SDSL‐EPR) . This SDSL‐EPR technology may be helpful for studying the effect of orientation distributions of trapped enzymes on their bioactivity after encapsulation by a MOFs.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Av ery recent and emerging application is the engineering of rigid MOF layers as exoskeleton to protect fragile biomacromolecules,i ncluding enzymes,t hrough ad e novo embedding strategy. [10][11][12][13][14][15] In this approach, biomacromolecules of different size and even viruses and cells were encased within MOFs that possessed significantly smaller pore dimensions than themselves. [15][16][17][18][19] It was demonstrated that the porous MOF exoskeletons could not only improve the stability of the encapsulated enzymes through structural confinement, but also allow selective transport of the guest via the accessible micropores network of the exoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] However,t hese initial studies mainly focused on embedding functional enzymes in protective MOF cages without emphasizing the embedding patterns,a nd only limited consideration has been given to the conversion of the enzymatic biofunctionality after entrapment by aMOFs.This is worthy of attention, as the de novo encapsulating process could result in inactivation of enzymes due to their fragile nature.Indeed, we noticed that in some cases the enzymes are partially or even completely inactive when encapsulated within zeolitic imidazolate framework-8 (ZIF-8) crystals (see below), aw idely used exoskeleton for in situ enzyme encapsulation. [10,11,[14][15][16][17][18][19][20][21][22][23][24][25][26] In this work, we sought to reveal how embedding patterns influence the biofunctionality of enzymes encapsulated within ZIF-8 and to develop an ew strategy to produce enzymes@ZIF-8 biocomposites that maintain high enzymatic activity.W ec hose six typical enzymes as models, glucose oxidase (GOx), cytochrome C( Cyt C), horseradish peroxidase (HRP), catalase (CAT), urate oxidase (UOx) and alcohol dehydrogenase (ADH). These enzymes are extremely valuable across aw ide range of industries,i ncluding biofuel, food, and biosensing, and as therapeutics in the pharmaceutical industry.O ur findings show that ZIF-8-embedded enzymes (enzymes@ZIF-8), wherein the enzymes were encapsulated through rapid self-triggered nucleation around their surface,maintain high enzymatic activity,comparable to the free enzymes.I nt he other encapsulation process,w here the MOF nucleated as they normally would in the absence of the enzymes,a nd the enzymes were encapsulated through slow coprecipitation, the obtained enzymes@ZIF-8 tended to be inactive due to unfolding effects and competing coordination caused by the 2-methyl imidazole (HmIM) ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Aufgrund der Interferenzen der MOF‐Hintergrundsignale ist es allerdings sehr schwierig, die Orientierung von MOF‐eingebetteten Enzymen zu bestimmen. Glücklicherweise gelang 2018 die Charakterisierung der Orientierung MOF‐eingebetteter Enzyme mithilfe von ortsgerichteter Spinmarkierung in Kombination mit Elektronenspinresonanz (SDSL‐EPR) . SDLS‐EPR könnte sehr hilfreich für das Studium von Auswirkungen der Orientierungsverteilung auf die biologische Aktivität sein.…”
Section: Zusammenfassung Und Ausblickunclassified